Invocation of the Sun in the Gayatri Mantra and in Latvian Folksongs - Agita Baltgalve (Dr. Chinmay Pandya, 2024)
The close affinity between Sanskrit and European languages has been proven a long time ago, and many researches about Central European languages and Lithuanian language have been published in this regard. However, there are just a few comparative works about Sanskrit and Latvian language, mainly dictionaries or studies on morphology, phonetics, and transcription. This research deals with lexicogrammatical and semantic aspects of Sanskrit and Latvian that have not yet been properly analyzed by other scholars. In this regard, the research provides a unique contribution to the comparative literature and linguistic studies. Besides, the author has chosen a new perspective to view the Sun in the religious folk culture, correlating it with linguistic semantics in a close-to-text analysis of three poetic texts - the Gayatri mantra and two Latvian folksongs. The main goal of this research is to discover and to describe similarities and differences in literary means of expression, grammar and lexica of Sanskrit and Latvian in order to display the spiritual attitude toward the Sun in both cultures. Syntactic parts in both languages are compared, starting from the level of words, phrases, and sentences to the level of the writing as a whole. Although phonetics, intonation, and meter also constitute an essential part of mantras and folksongs, however, they will not be discussed in this article. It would rather be an object of a field research about oral traditions of the folk culture. [ In Latvian: Sanskrita un Eiropas valodu ciesa radnieciba ir pieradita jau sen, un ir publiceti daudzi petijumi par Centraleiropas un lietuviesu valodam. Tacu ir tikai dazi salidzinoša aspekta darbi par sanskritu un latviesu valodu, galvenokart, vardnicas vai raksti par morfologiju, fonetiku un transkripciju. Saja petijuma aplukotas sanskrita un latviesu valodas leksikogrammatiskas un semantiskas iezimes, kuras citi valodnieki vel nav pienacigi analizejusi. Lidzi ar to raksts sniedz unikalu ieguldijumu salidzinošas literaturzinatnes un lingvistikas joma. Turklat autore piedava jaunu skatijumu uz saules telu religiskaja tautas kultura, sasaistot to ar lingvistisko semantiku, tekstam tuva analize salidzinot tris poetiskus darbus - Gajatri mantru un latviesu tautasdziesmas Lec, Saulite un Spigulo, Saulite. Si petijuma galvenais merkis ir atklat un aprakstit lidzibas un atskiribas sanskrita un latviesu valodas literarajos izteiksmes lidzeklos, gramatika un leksika, tai par laika paradot garigo attieksmi pret sauli latviesu un indiesu kulturas. Sintaktiska aspekta tiek vispirms salidzinati vardi, frazes un teikumi, bet pec tam apskatiti ari visi panti to veseluma. Fonetika, intonacija un metrika ari ir butiska mantru un tautasdziesmu sastavdala, tomer saja raksta tas netiks detalizetas. Sadam izpetes objektam butu vairak atbilstos lauka petijums par tautas kulturas mutvardu tradicijam.]